A Hybrid Joint Based Controller for an Upper Extremity Exoskeleton - Ismail, Mohd Khairuddin; Zahari, Taha; Anwar, P. P. Abdul Majeed; Abdel Hakeem, Deboucha; Mohd Azraai, M. Razman; Abdul Aziz, Jaafar; Zulkifli, Mohamed (IOP Publishing, 2016)
This paper presents the modelling and control of a two degree of freedom upper extremity exoskeleton. The Euler-Lagrange formulation was used in deriving the dynamic modelling of both the human upper limb as well as the exoskeleton that consists of the upper arm and the forearm. The human model is based on anthropometrical measurements of the upper limb. The proportional-derivative (PD) computed torque control (CTC) architecture is employed in this study to investigate its efficacy performing joint-space control objectives specifically in rehabilitating the elbow and shoulder joints along the sagittal plane. An active force control (AFC) algorithm is also incorporated into the PD-CTC to investigate the effectiveness of this hybrid system in compensating disturbances. It was found that the AFC- PD-CTC performs well against the disturbances introduced into the system whilst achieving acceptable trajectory tracking as compared to the conventional PD-CTC control architecture.